Essential pharmacokinetics : a primer for pharmaceutical scientists - Loftsson, Thorsteinn (Amsterdam ; Boston : Elsevier, 2015)
Essential Pharmacokinetics: A Primer for Pharmaceutical Scientists is an introduction to the concepts of pharmacokinetics intended for graduate students and new researchers working in the pharmaceutical sciences. This book describes the mathematics used in the mammillary model as well as the application of pharmacokinetics to pharmaceutical product development, and is useful as both a self-study and classroom resource. Content coverage includes detailed discussions of common models and important pharmacokinetic concepts such as biological half-life, clearance, excretion, multiple dosage regimens and more. Numerous equations, practical examples and figures are incorporated to clearly illustrate the theoretical background of pharmacokinetic behavior of drugs and excipients.
7.57.6; A; B; 7.7; A; B; C; 7.8; A; B; C; 7.9; A; B; C; 7.10; 7.11; 7.12; 7.13; 7.14; 7.15; 7.16; 7.17; Appendix II: Symbols and Abbreviations; Index.
Off-Campus Access: Athens ID and Password Required
On-Campus Access: No User ID or Password Required
Includes bibliographical references and index.
Mode of access: Internet
Keywords: Pharmacokinetics; MEDICAL -- Pharmacology; Pharmacokinetics; Pharmacokinetics; Electronic books